Synthesis and application of P4VP based block copolymers from supercritical CO2 - Larder, Ryan (2021)
In recent years, supercritical carbon dioxide (scCO2) has proven to be an efficient and green medium to produce block copolymer microparticles with internal nanostructures. When conducting controlled radical dispersion polymerisations, the unique physical properties of scCO2 allow for spontaneous self-assembly of the block copolymers within the confines of the stabilised microparticles. This has successfully yielded highly pure hierarchically structured polymers in a single reaction procedure, without the need for any non-renewable or toxic solvents. Moreover, preliminary tests show that when a poly(4-vinylpyridine) (P4VP) block is incorporated into the polymer, the resulting microparticles can be capable of directing the formation of inorganic materials. Selective association of inorganic components to the pyridinyl nitrogen moieties of the P4VP can allow the polymer materials to act as structural templates to fabricate nanoscale functional materials.